Election Governance as a Collective Political Process: A Study of Local Political Management in North Central Timor Regency - Ignasius Usboko; Melkianus Suni; Surya Yudha Regif (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This rticle aims to understand the regional elections as a collective political process strough the practice of local political management involving the milenial generation and utilization of social media, particularly face book in the North Central Timor Regency (TTU). Based on the results of a quantitave study involving 200 milenial respondents who participate in the 2020 TTU regional elections it was found that the political participation of the younger generation is very high and diverse including rules as simpathizers, organizer, success team and party members. Social media has become the main channel mediating political information, building social - political networks and strengthening the relationship between voters and candidates. Local political governance in regional elections takes place through interactions based on social networks, collective values and informal consensus. This article suggest the importance of designing regional elections as a collaborative space that recognize the rule oh the younger generation and the power of digital communication in realizing substantial and inclusive local democrazy.